Measurement of Bd mixing using opposite-side flavor tagging - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
We report on a measurement of the Bd0 mixing frequency and the calibration of an opposite-side flavor tagger in the D0 experiment. Various properties associated with the b quark on the opposite side of the reconstructed B meson are combined using a likelihood-ratio method into a single variable with enhanced tagging power. Its performance is tested with data, using a large sample of reconstructed semileptonic B→μD0X and B→μD*X decays, corresponding to an integrated luminosity of approximately 1fb-1. The events are divided into groups depending on the value of the combined tagging variable, and an independent analysis is performed in each group. Combining the results of these analyses, the overall effective tagging power is found to be εD2=(2.48±0.21-0.06+0.08)%. The measured Bd0 mixing frequency Δmd=0.506±0.020(stat)±0.016(syst)ps-1 is in good agreement with the world average value. © 2006 The American Physical Society.